Using of cerebrolysin in patients with epilepsy - A. S. Kotov (Русский журнал детской неврологии, 2018)
Objective: to assess the efficiency and tolerability of cerebrolysin in patients with epilepsy.Materials and methods. Sixty six epileptic patients with low Montreal Cognitive Assessment results (less than 26 scores) were studied. The examination included neurologic examination, routine electroencephalography and/or video-electroencephalography monitoring, magnetic resonance imaging of the brain, assessment of clinical and biochemical blood tests. Criteria for exclusion were processual brain damage and noncompliance. All patients were assigned cerebrolysin 10 ml intravenous, an assessment of seizures frequency and cognitive functions was performed 1 and 3 months after the 1st visit. All the procedures of the study were performed by 38 patients out of 66.Results. In a group of patients with Alzheimer’s dementia there was a statistically insignificant tendency to decrease the final score over time (obviously associated with the progression of the disease); in the group of patients with brain damage the results of testing were improved, presumably related to the processes of neuroplasticity induced by cerebrolysin.Conclusion. Our results suggest that cerebrolysin is well tolerated and does not increase the frequency of epileptic seizures in patients with stable epilepsy (with no risk of developing status epilepticus) and cognitive disorders.